Cellular therapies in no-option critical limb ischemia: present status and future directions - Kwiatkowski, Tomasz; Zbierska-Rubinkiewicz, Katarzyna; Krzywoń, Jerzy; Szkółka, Łukasz; Kuczmik, Wacław; Majka, Marcin; Maga, Paweł; Drelicharz, Łukasz; Musiałek, Piotr; Trystuła, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Critical limb ischemia – an advanced stage of lower extremity arterial disease with presence of rest pain and/or ischemic ulcers – remains an important cause of major amputations and disability in developed societies. Novel treatment strategies are urgently needed to prevent (or delay) amputations in particular for patients in whom effective revascularization is no longer feasible for anatomic and/or technical reasons (no-option critical limb ischemia – N-O CLI). Cellular therapies have been gaining the growing attention of researchers and clinicians in the last two decades. Several cell types have been used in pre-clinical and clinical studies, and a number of mechanisms have been proposed to contribute to vascular reparation and regeneration in N-O CLI. Although early trials suggested clinical improvement with use of cell-based therapies in N-O CLI, meta-analyses that included randomized controlled trials have not provided definitive conclusions. Fundamental limitations have involved poorly defined cell lines/populations, limited numbers of study participants and limited follow-up periods, and enrolling patients “too sick to benefit” (such as those in Rutherford class 6). Recent advances include standardized “unlimited” sources of therapeutic cells and better understanding of mechanisms that may contribute to vascular reparation and regeneration. Furthermore, based on recent pre-clinical and clinical studies, cell-free preparations (such as microvesicle-based) are being increasingly developed along with advanced therapy medical products consisting of engineered cells and pro- angiogenic factors.